The contribution of mentorship to personal and institutional development at the Westville Campus of the University of Kwa-Zulu Natal - Essack, Shaheeda (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- Stellenbosch University 2006.